Molecular identification and phylogenetic analysis of Chlamydophila abortus isolated from sheep and goats - Fariba Taheri; Abdolghaffar Ownagh; Karim Mardani (The Iranian Journal of Veterinary Science and Technology, 2021)
Chlamydophila abortus is one of the major causes of pregnancy failure (abortion) in sheep and goats in many countries. In the present study, milk samples from sheep and goat herds of West Azerbaijan, Iran were examined for C. abortus using PCR and nucleotide sequencing. A total number of 360 milk samples were randomly collected from sheep (n=180) and goats (n=180) of three different regions of West Azerbaijan province during 2018. DNA was isolated from samples and the nested-PCR was employed targeting the 16S rRNA gene for detection of Chlamydia spp. The omp gene was amplified and sequenced for the characterization of detected C. abortus.The results showed that 8.61% (95% CI: 6.13%–11.96%) of the examined samples (11.67% sheep and 5.56% goat milk samples) were positive for C. abortus. The frequency of positive samples in the central region was significantly higher than in other regions. Positive samples for C. abortus from animals with a history of abortion were significantly higher than those without a history of abortion. Positive samples in autumn were significantly higher than the other seasons and also, in animals more than four years old were significantly higher than other age groups. Sheep infection was significantly higher than the goats. Phylogenetic analysis based on the helicase gene showed that two sequenced isolates clustered closely with the other C. abortus isolates reported in the GenBank. In conclusion, small ruminants in West Azerbaijan province were contaminated with C. abortus and they could shed this organism into the milk.